Menggali Peran Penerapan GHRM dan CSR Pada Apotek Ananda Farma - Alif Ananda P; Calvin Owen; Fikra Terisha A; Gilbert Chryshologus; Antony Sentoso (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
In developing business management, it is committed to exploring Green Human Resource Management (GHRM) as a way to improve Corporate Social Responsibility (CSR) practices, both internally such as company employees and external parties such as stakeholders and the wider community. Recent research focuses on the impact of corporate social responsibility (CSR), green human resource management (GHRM), and green innovation on corporate sustainability. The aim of this research is to determine the extent of the implementation of GHRM and CSR for corporate sustainability which refers to strategies and practices designed by a company to provide long-term benefits for all stakeholders, including shareholders, employees, customers and the community around the company's business activities. as well as marketing mix combinations in the business world. The method used in this research is descriptive qualitative. Researchers obtained the information needed by conducting direct interviews with the management of the Ananda Farma pharmacy. The process of collecting information in this study went through the first stage, by conducting a literature audit related to studies on GHRM and CSR. This study reveals that companies that invest in CSR activities in developing countries can significantly improve their performance and contribute to the overall welfare of society. In conclusion, this research also highlights the importance of CSR in meeting the needs of vulnerable communities in developing countries and highlights the importance of business practices in increasing customer satisfaction, loyalty and corporate social responsibility.